Emerging research and policy themes on academic integrity in the age of Chat GPT and generative AI / Sterling Plata, Maria Ana De Guzman and Arthea Quesada - Plata, Sterling; De Guzman, Maria Ana; Quesada, Arthea (Universiti Teknologi MARA, 2023)
Universities are increasingly concerned with the impact of Generative AI, such as Chat GPT, on cheating and other violations of students' academic integrity. However, research is scarce regarding the responses of universities on this issue. In addition, the increase in studies on GenAI invites a systematic review of themes and trends to update researchers who wish to embark on this emerging research area. This paper reviews 37 articles on academic integrity in the Age of Gen AI and presents the approaches of the top 20 global universities to mitigate the impact of artificial intelligence tools on students’ intellectual integrity and learning. The results showed three themes both in the systematic review of the literature and the content analysis of the policies of the top 20 global universities: enforcement of academic integrity, education of faculty and students on ways to avoid academic misconduct, and encouragement of using Gen AI tools in the academe and the workplace, for productivity. This paper proposes a 3E Model for higher education institutions to start a discussion on creating a roadmap to ensure academic integrity, explore ways to improve classroom assessment practices, and encourage exploration of evolving Gen AI tools. In addition, the categories found in this study may be used by universities in updating their research agenda on Generative AI.